Examining the doctoral viva: Perspectives from a sample of UK academics (UCL Press, 2015)
The doctoral viva voce examination has existed in Britain since the PhD (or DPhil) was introduced at Oxford University almost a hundred years ago. However, despite some recent research studies, it seems that the viva remains somewhat under-researched and that viva voce examinations continue to take place according to largely unchanged and unchallenged procedures. This paper presents evidence collected via questionnaire and interview from a sample of UK academics working in education departments at 16 universities in England. It is shown that individuals within the sample hold contrasting views about the purpose, value, and degree of reliability associated with oral assessment at doctoral level. The paper critically examines eight aspects of the viva's design, purpose, conduct, and outcomes, under such headings as 'examiner judgement', 'examiner behaviour/attitudes' and 'the viva as opportunity'. The question of whether examiners should have the power to waive the viva under certain circumstances is also addressed. Rather than attempting to provide definitive answers to such questions, the paper highlights a series of inter-related issues which seem problematic. The author's intention is to spark further discussion in academia about the viva's current and possible future content, conduct, and purposes.